Managing dental and skeletal development in patients with hemifacial microsomia - Alshehri, Ghadeer Z.; Almusharraf, Sakinah M.; Almutairi, Hajer H.; Alshammari , Ebtehal L. (International Journal Of Community Medicine And Public Health, 2024)
Hemifacial microsomia (HFM) is a congenital condition characterized by the underdevelopment of one side of the face, impacting the ear, mouth, and jaw areas. This anomaly, second only to cleft lip and palate in prevalence, presents significant challenges in dental and skeletal development. Early diagnosis, primarily through advanced imaging techniques such as 3D computed tomography (CT) scans and magnetic resonance imaging (MRI), is crucial for identifying the extent of anomalies and planning effective interventions. The condition involves complex dental issues including malocclusion, missing teeth, and delayed dental eruption, necessitating early and targeted orthodontic treatments. Functional appliances, space maintainers, and braces are commonly used to guide dental arch development and correct alignment, leveraging the natural growth phase of the patient. Surgical interventions play a pivotal role in managing severe skeletal deformities. Preventive strategies, including regular dental check-ups, proper oral hygiene practices, and preventive treatments such as fluoride applications and dental sealants, are vital in minimizing complications and ensuring long-term oral health. Educating patients and their families on the importance of oral hygiene and routine dental care is crucial for maintaining dental health and preventing future issues. Continuous monitoring and follow-ups allow for timely adjustments to treatment plans, enhancing the effectiveness of interventions and supporting optimal growth and development. Overall, the management of dental and skeletal anomalies in hemifacial microsomia involves a combination of early diagnosis, orthodontic and surgical treatments, and preventive care, all of which are integral to improving outcomes and quality of life for affected individuals.